PRODUCT VALUE PROPOSITION, SOURCE INFORMATION, TRUST AND PURCHASE DECISION IN UMRAH TRAVEL SERVICES: A SYSTEMATIC LITERATURE REVIEW - Hasrun Afandi UmpuSinga; Iskandar Ali Alam; Habiburrahman; Andala Rama Putra Barusman (Institut Agama Islam Negeri Metro, 2026)
This study aims to synthesize international journal articles on the relationships among Product Value Proposition, Source Information, Trust, Purchase Intention, and Purchase Decision in the context of Umrah travel services. A Systematic Literature Review (SLR) was conducted, analyzing 42 peer-reviewed articles retrieved from Scopus, Web of Science, ScienceDirect, Emerald Insight, Taylor & Francis Online, SpringerLink, Wiley Online Library, and Google Scholar during 2003–2024, following the PRISMA 2020 guidelines. The findings indicate that Product Value Proposition and Source Information act as initial stimuli reducing uncertainty and forming Trust. Trust then strengthens Purchase Intention, which subsequently leads to Purchase Decision. This study contributes to the literature by integrating Asymmetric Information Theory, Signaling Theory, Trust Theory, and the Theory of Planned Behavior into a conceptual framework specific to Umrah travel services, addressing both theoretical gaps and practical implications for PPIU providers.